2020
DOI: 10.1088/2053-1591/ab6f41
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural, mechanical and tribological characterization on the Al based functionally graded material fabricated powder metallurgy

Abstract: The characteristics of composite materials can be enhanced by using it as functionally graded composites (FGM). In this work, four-layer FGMs are produced by using aluminum, silicon carbide, and magnesium peroxide. The entire fabrication process has been performed through the sintering process, in which, the powder methodology is used to blend the particles of each material. During the fabrication of FGM, three parameters such as sintering time, sintering temperature and compacting pressure are considered. Fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…However, the sintered FGCM had significant porosities, and the amount of porosity increased with increasing ceramic content. In another study, Srinivas et al [140] fabricated four-layered FGCMs with individual layer compositions of 100%Al, 90%Al + 10%SiC, 90%Al + 5%SiC + 5%MgO 2 , and 85%Al + 5%SiC + 10%MgO 2 , respectively. The effect of various processing parameters such as sintering time, temperature and compaction pressure on the mechanical and wear characteristics were systematically studied.…”
Section: Metal-metal and Metal-ceramic Fgcmsmentioning
confidence: 99%
“…However, the sintered FGCM had significant porosities, and the amount of porosity increased with increasing ceramic content. In another study, Srinivas et al [140] fabricated four-layered FGCMs with individual layer compositions of 100%Al, 90%Al + 10%SiC, 90%Al + 5%SiC + 5%MgO 2 , and 85%Al + 5%SiC + 10%MgO 2 , respectively. The effect of various processing parameters such as sintering time, temperature and compaction pressure on the mechanical and wear characteristics were systematically studied.…”
Section: Metal-metal and Metal-ceramic Fgcmsmentioning
confidence: 99%
“…80 Traditional sintering techniques include hot isostatic pressing (HIP), mechanical alloying, and hot extrusion. 78 Srinivas et al 81 studied the mechanical, microstructural, and tribological characteristics of four-layered FGMs manufactured using powder metallurgy. Four layers of FGM were produced using three different materials: aluminium (Al), magnesium peroxide (MgO 2 ), and silicon carbide (SiC).…”
Section: Powder Metallurgymentioning
confidence: 99%
“…Nowadays, materials like aluminum (Al), copper (Cu), and titanium are utilized in many industrial applications like piston cylinders, flywheels, piping systems, cylinder liners, crank shafts, etc., wherein certain characteristics such as low weight, high impact strength, and high mechanical strength are desired. 8,18 Al is among the highly utilized materials for aircraft, marine, and automotive applications due to its lower weight but it shows restraint in its tensile and impact strength. 9 To overcome these limitations, Al-based alloys and composites were evolved.…”
Section: Introductionmentioning
confidence: 99%
“…Mechanical strength at different layers increases with an increase in nickel content. Srinivas and Balakrishna 18 studied the tribological properties of Al-based FGMs reinforced with SiC and magnesium peroxide (MgO 2 ) particles. The authors observed the decrease in wear rate at outer layers due to the presence of SiC particles.…”
Section: Introductionmentioning
confidence: 99%